Drug and Substance Use and Its Predictors among the Youth in Nyamira Sub County, Nyamira - Wando, S. O.; Asito, S. A.; Aminer, T. J. (www.strategicjournals.com, 2018)
Substance and drug use is one of the emerging public health problems among the youth in Kenya. Moreover, it is associated with a myriad of medical effects including psychiatric problems, organ failures in addition to lethargy, decreased academic performance and risk of contracting sexually transmitted infections. Although substance and drug use has been associated with these problems, the magnitude of substance and drug use and its predictors has not been investigated in poor resource setting in rural areas of Kenya. Therefore, this study was designed to determine the prevalence of substance and drug use and identify their predictors among the youth in a poor resource setting in Nyamira Sub-County in Nyamira County. To this end this study used a cross-sectional study to evaluate the prevalence of substance and drug use and their predictors in Nyamira slums. The result of this study revealed that there were more males (60.39%) relative females (28.57%) using drugs and substances (p<0.001). A majority of study participants (94.7) had their drug and substance use debut before 20 years. Being divorced/separated/widowed (3.14, 95%CI 1.27-7.78), non-religious (70.2, 95% CI 7.28-676.83), being a Muslim (OR 3.15, 95%CI 0.61-16.31) and residing in urban area relative to rural (OR 0.84, 95%CI 0.53-1.31) were positively associated with drug and substance use. In conclusion, this study found that the prevalence of drug and substance use was high in males relative to females. The main predictors of drug and substance use included residing in urban area, being a Muslims or being non-religious and being divorced/separated or widowed. These data therefore indicated the drug and substance use was influenced by a multiplicity of factors. The results of this study would be important for Ministry of health or government or policy makers in formulating age friendly and family based intervention strategies to curb substance and drug use among the youth and increase public awareness.
Keywords: drug; substances use; predictors; Youth